Новітня історіографія культурно-просвітницької діяльності церковних православних братств Волинської губернії у другій половині ХІХ - на початку ХХ ст. - Сажок, Оксана; Sazhok, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2013)
Проаналізовано дослідження останніх двадцяти років з історії культурно-просвітницької діяльності церковних православних братств Волинської губернії у другій половині ХІХ – на початку ХХ ст. Виявлено і розглянуто наукові та історико-краєзнавчі праці сучасних українських, російських, білоруських і польських дослідників із зазначеної проблематики.

Versatile reveal the history of the Russian Orthodox Church and religious organizations received attention in the scientific and local historical works of modern Belarusian, Russian and Polish investigators, but such exploration because of their goals and objectives will not affect features of cultural and educational asceticism Volyn fraternities. Some aspects specified topics raised in the books of Ukrainian scientists and ethnographers on the history of the Orthodox Church in Ukraine and Volyn. In recent Ukrainian historiography of interest are works that reveal only a few signs of life in the fraternities in Volyn diocese. As a result of processing and critical rethinking of historiographical works found that cultural and educational activities of the church orthodox fraternities Volyn province of the second half of the XIX and at the beginning of XX century been the subject of special study, only occasionally reported in the general research on the history of the Orthodox Church and the fraternities movement in the Russian Empire, as well as individual works of Volyn local history and monuments.
Recent Historiography of Cultural and Educational Activity of Volyn Province Church Orthodox Fraternities on the Second Half of the XIX and at the Beginning of XX Century
Keywords: Волинська губернія; церковні православні братства; культурно-просвітницька робота; бібліотеки; історіографія; Volyn province; church orthodox fraternities; cultural and educational work; libraries; historiography